FAKTOR-FAKTOR YANG MEMPENGARUHI SUBTIPE GEJALA MOTORIK PENYAKIT PARKINSON - Attiya Istarini; Yuliarni Syafrita; Restu Susanti (Universitas Fort De Kock, 2020)
Background: Parkinson's disease (PD) is a chronic neurodegenerative disease that manifests as movement disorders. Based on motor symptoms, PD is classified into subtypes of tremor and postural instability gait disorders (PIGD). The motor symptoms subtype is a predictor of disease progression, therapeutic response, and quality of life for Parkinson's patients. The purpose of this study is to identify some factors that influence motor symptoms in Parkinson's disease.Methods: This research use cross sectional design. Samples were selected by consecutive sampling method that met the inclusion and exclusion criteria. Research subjects were 58 people. Statistical analysis using SPSS. p values <0.05 were considered statistically significant.Results: This research include 58 patients, 55.2% were men with range of age 63.5 ± 8.5 years old. The mean age at onset was 57.9 ± 9.5 years and duration of disease 6.1 ± 4.6 years. Motor symptoms 53.4% dominant tremor. There was a significant relationship between disease stage and motor symptom subtypes (p <0.001). There is no relationship between the patient's age, age at onset and duration of the disease with motor symptom subtypes.Conclusions: There is a relationship between disease stage and motor symptom. The patient's age, age at onset and duration of the disease are not related to the motor symptoms of Parkinson's patients.